2003
DOI: 10.1249/01.mss.0000084522.14168.49
|View full text |Cite
|
Sign up to set email alerts
|

Athletes with Exercise-Associated Fatigue Have Abnormally Short Muscle DNA Telomeres

Abstract: These findings suggest that skeletal muscle from symptomatic athletes with FAMS show extensive regeneration which most probably results from more frequent bouts of satellite cell proliferation in response to recurrent training- and racing-induced muscle injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 20 publications
4
67
0
1
Order By: Relevance
“…Athletes suffering FAMS have history of high-volume training for many years and are chronically fatigued. Histological evidence indicates extensive muscle regeneration (Collins et al, 2003;490 Vihko et al, 1978490 Vihko et al, , 1979, which results in an elevated demand for satellite cell proliferation (Collins et al, 2003). Consequently, if muscles are damaged over an extended period of time, telomeres can be expected to be shorter in skeletal muscle of FAMS athletes.…”
Section: ) In Contrast To Skeletal Muscle Cells Tl Mean Values In mentioning
confidence: 99%
See 3 more Smart Citations
“…Athletes suffering FAMS have history of high-volume training for many years and are chronically fatigued. Histological evidence indicates extensive muscle regeneration (Collins et al, 2003;490 Vihko et al, 1978490 Vihko et al, , 1979, which results in an elevated demand for satellite cell proliferation (Collins et al, 2003). Consequently, if muscles are damaged over an extended period of time, telomeres can be expected to be shorter in skeletal muscle of FAMS athletes.…”
Section: ) In Contrast To Skeletal Muscle Cells Tl Mean Values In mentioning
confidence: 99%
“…Consequently, if muscles are damaged over an extended period of time, telomeres can be expected to be shorter in skeletal muscle of FAMS athletes. To prove this hypothesis, (Collins et al, 2003) compared TRF min and TRF mean values in vastus lateralis muscle from 13 athletes aged 42.0±10.2 years suffering from FAMS with 13 healthy controls matched for age and, according to the authors, also for training volume. Type I fiber ("slow 495 twitch") proportions were similar in the FAMS and control group.…”
Section: ) In Contrast To Skeletal Muscle Cells Tl Mean Values In mentioning
confidence: 99%
See 2 more Smart Citations
“…When satellite cells were heavily recruited for regenerative events, as in the skeletal muscle of athletes, telomere length was found to be either significantly shortened or maintained, and was even found to be longer compared to that in non-trained individuals. Evidence suggested that physical activity may preserve or lengthen telomeres, although exhaustive exercise, such as that performed by athletes, may shorten the telomeres in skeletal muscle (23). Moreover, exercise induces autophagy (24) also demonstrated that SRM may exert multiple effects on the body, including pain reduction, tissue regeneration, immune system modulation and possible telomere lengthening.…”
Section: Slowing the Aging Process Of Stem Cellsmentioning
confidence: 99%